2017
DOI: 10.1248/bpb.b17-00271
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin I Overcomes EMT-Associated Resistance to Erlotinib in Lung Cancer Cells <i>via</i> IL-6/STAT3 Pathway Inhibition

Abstract: Acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) is the most important limiting factor for treatment efficiency in EGFR-mutant non-small cell lung cancer (NSCLC). Much work has linked the epithelial-mesenchymal transition (EMT) to the emergence of drug resistance, consequently, ongoing research has been focused on exploring the therapeutic options to reverse EMT for delaying or preventing drug resistance. Polyphyllin I (PPI) is a natural compound isolated from Pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…This enhanced the effect of erlotinib on lung tumor growth both in vitro and in vivo. Thus, combined PPI and erlotinib strengthened drug response and provided a novel therapeutic for patients with lung cancer [57]. Our findings suggested that PPI sensitized or enhanced the effect of enzalutamide on controlling CRPC cell growth or vice versa by targeting p65, HOTAIR, and MUC1 regulatory signaling axis, implying a potential synergy between PPI and enzalutamide in anti-androgen-resistant ways.…”
Section: Discussionmentioning
confidence: 69%
“…This enhanced the effect of erlotinib on lung tumor growth both in vitro and in vivo. Thus, combined PPI and erlotinib strengthened drug response and provided a novel therapeutic for patients with lung cancer [57]. Our findings suggested that PPI sensitized or enhanced the effect of enzalutamide on controlling CRPC cell growth or vice versa by targeting p65, HOTAIR, and MUC1 regulatory signaling axis, implying a potential synergy between PPI and enzalutamide in anti-androgen-resistant ways.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, polyphyllin I, a steroidal saponin derived from Paris polyphylla , has shown anti inflammatory and anticancer properties. It was suggested that polyphyllin I, which reversed EMT by modulating the IL‐6/STAT3 pathway, served as a novel solution to conquer EGFR‐TKI resistance in non–small‐cell lung cancer (Figure ). Therefore, combined treatment with polyphyllin I and erlotinib is a promising therapy for lung cancer patients to strengthen drug efficacy and reduce drug resistance .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…It was suggested that polyphyllin I, which reversed EMT by modulating the IL‐6/STAT3 pathway, served as a novel solution to conquer EGFR‐TKI resistance in non–small‐cell lung cancer (Figure ). Therefore, combined treatment with polyphyllin I and erlotinib is a promising therapy for lung cancer patients to strengthen drug efficacy and reduce drug resistance . The other compound, quercetin, is a flavonoid widely distributed in fruits, vegetables, and beverages that shows antioxidative, anti inflammatory, and anticancer properties.…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…It possesses anti‐cancer activities and can reverse EMT by blocking the IL6/STAT3 pathway to overcome NSCLC cell resistance to EGFR‐TKIs. The combined use of PPI and erlotinib can possibly reverse the acquired resistance to EGFR‐TKIs and prolong patient life …”
Section: Il‐6‐related Progress In Tumor Treatments In Internal Medicinementioning
confidence: 99%